Isolation of high-quality ribonucleic acid and complementary deoxyribonucleic synthesis from Oryza Sativa - Anis Adibah Osman, 1989- author; Faezah Mohd. Salleh, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (2014)
Thesis (Sarjana Sains (Bioteknologi)) - Universiti Teknologi Malaysia, 2014